(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: An international epidemic known as dental anxiety impacts individuals of all ages worldwide. Children, adults, and society as a whole may all be significantly impacted by the disorder, which has a negative influence on quality of life related to dental health. Dental anxiety has a complex aetiology, making it difficult to treat with a single therapy, which is a major deterrent to getting dental care. The paediatric dentist can determine the best management options by properly evaluating the patient and determining their source and level of anxiety. Estimates of dental anxiety’s prevalence may also be affected by the techniques employed to measure it. Aim: This systematic review and meta analysis was carried out to evaluate the efficacy of several projective dental associated anxiety measurement tools used in children as well as evaluate the many accessible dental anxiety scales. Methods and materials: The articles were chosen by two independent reviewers in two stages. In the first stage, each reviewer individually searched titles and abstracts according to the eligibility requirements. Articles were added to the systematic review when a third evaluator made a consensus decision in cases of disagreements. The preselected papers were subjected to full text examination by the same reviewers in phase two in order to determine eligibility and extract pertinent data. We employ the PICO framework, which compared (C) the different types of tools for measurement of anxieties like FIS, VPT, and RMS. the outcome (O) was anxiety scores in the population (P) consisting of children in the age range of 3 to 15 years, with no intervention (i) administered. For this meta-analysis, descriptive cross-sectional research were used. Two reviewers extracted the following data from the selected articles: author(s) and year of publication, design of study , objective of research, age and size of population, dental related anxiety measuring tools applied and outcome Results: 13 studies were ultimately chosen for comprehensive assessment. The VPT and the FIS were examined on a combined total of 295 and 293 kids, respectively. In the population under investigation, there was a computed average difference between the two tools of 0.14 (95% CI: 0.27-0.49). There was no significant variance statistically (p value = 0.76), indicating that both scales are equally accurate in determining the level of anxiety in the paediatric population. There were 209 kids evaluated for the RMS and VPT tools in total. In the population under investigation, there was a computed average difference between the two tools of 0.29 (95% CI: 0.81-0.22). Both were on par, showing that both were equally reliable (p=0.33). There were 209 kids evaluated for the RMS and VPT tools in total. In the population under investigation, there was a computed average difference between the two tools of 0.29 (95% CI: 0.81-0.22). Conclusion: We draw the conclusion that VPT, FIS, and RMS scales are the most often used projective measures in paediatric dentistry. These three tools are equally useful in determining how anxious kids are about visiting the dentist. The findings from this paper can be used by academics, clinicians, and psychologists to choose the best dental related anxiety evaluation system for their specific needs. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.S -S